From the Trees of Recife (1924) to the Coastal Forest of the Northeast (1937): Ecology, Tropics, and Region in the Work of Gilberto Freyre - Schneider, Alberto Luiz (2023)
The aim of this article is to investigate Gilberto Freyre's ecological and environmental discourses in two distinct but interrelated historical moments. In the first moment, this work analyzes newspaper articles published by the “Diário de Pernambuco” in the 1920s, particularly in 1924, when the young Freyre wrote a series of texts in defense of the arborization of Recife. The second moment, in the 1930s, was marked by the publication of "Nordeste" in 1937, in which the author criticized the environmental devastation of the coastal strip, specifically the sugar mill owners. Freyre approached ecological questions within the intellectual and political architecture that characterized his work, intertwined with the defense of the tropics e Iberian traditions.